Muddy Waters : the mojo man. - Tooze, Sandra (ECW, 1997)
Born and raised on a Mississippi plantation, Muddy Waters was discovered in 1941 and two years later moved to Chicago where he pioneered what came to be known as urban, or electric, blues. This biography is based on original interviews with the legend.